Prefrontal Coding of Temporally Discounted Values during Inter-temporal Choice - Kim, Soyoun (2008)
Reward from a particular action is seldom immediate, and the influence of such delayed outcome on choice decreases with delay. It has been postulated that when faced with immediate and delayed rewards, decision makers choose the option with maximum temporally discounted value. We examined the preference of monkeys for delayed reward in a novel inter-temporal choice task and the neural basis for real-time computation of temporally discounted values in the dorsolateral prefrontal cortex. During this task, the locations of the targets associated with small and large rewards and their corresponding delays were randomly varied. We found that prefrontal neurons often encoded the temporally discounted value of reward expected from a particular option. Furthermore, activity tended to increase with discounted values for targets presented in the neuron's preferred direction, suggesting that activity related to temporally discounted values in the prefrontal cortex might determine the animal's behavior during inter-temporal choice.